OPTIMIZING SCIENCE LEARNING MOTIVATION THROUGH STRUCTURED AND AESTHETIC RECORDING STRATEGIES: A DESCRIPTIVE STUDY ON STUDENTS OF SMPN 1 PURWAKARTA - Christiana, Zubaidah (PT. Antis International Publisher, 2025)
Objective: This qualitative descriptive study aims to describe the process and impact of implementing a structured and aesthetic note-taking strategy to optimize students' motivation to learn science. Learning motivation is a crucial factor that often declines due to monotonous learning methods. Method: This study focuses on the experiences of eighth-grade students at SMPN 1 Purwakarta in adopting more organized and visually appealing note-taking habits. Data collection was conducted through three methods: participatory classroom observation, document analysis of student notebooks, and in-depth interviews with 15 students selected through purposive sampling. The collected data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. Results: The results show that students who implemented a structured and aesthetic note-taking strategy demonstrated positive changes in learning behavior. They became more active in processing information, rather than simply copying. Analysis of the notes revealed the use of information hierarchies, color coding, and simple diagrams that helped clarify complex science concepts. Interviews revealed that this strategy increased student interest because the note-taking process became more creative and personal. Students feel more confident and motivated to revisit their notes, which ultimately increases their persistence and engagement in science learning. Novelty: This study highlights the potential of structured and aesthetically enhanced note-taking strategies in improving student motivation and engagement in science, offering a creative and personalized approach to traditional note-taking methods.